1991
DOI: 10.1177/026142949100700306
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Gifted Children and Prodigies: Personological Concerns

Abstract: Monitoring has begun to be seen as a most viable option for the growth of gifted, talented children. This paper addresses personality issues and personological variables salient to the process of mentoring gifted children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…They can also help students objectively evaluate and set realistic objectives regarding their talents, which is particularly important to talented adolescents who are often concerned about how well their talents are developing or who may feel the need to mask such talents to gain peer acceptance (Buescher, 1991). Mentors can help gifted children deal with the risk of capitalizing on the wrong abilities (Shaughnessy & Neely, 1991), such as musically talented children who attempted to paint or draw (Sternberg, 1986), lack product-orientation and completion, and experience difficulty translating good ideas onto paper. M entoring works for gifted children because their approaches to learning are often nontraditional and misunderstood in the regular classroom.…”
Section: Affective and Social Characteristics Of Gifted Students Suppmentioning
confidence: 99%
See 2 more Smart Citations
“…They can also help students objectively evaluate and set realistic objectives regarding their talents, which is particularly important to talented adolescents who are often concerned about how well their talents are developing or who may feel the need to mask such talents to gain peer acceptance (Buescher, 1991). Mentors can help gifted children deal with the risk of capitalizing on the wrong abilities (Shaughnessy & Neely, 1991), such as musically talented children who attempted to paint or draw (Sternberg, 1986), lack product-orientation and completion, and experience difficulty translating good ideas onto paper. M entoring works for gifted children because their approaches to learning are often nontraditional and misunderstood in the regular classroom.…”
Section: Affective and Social Characteristics Of Gifted Students Suppmentioning
confidence: 99%
“…Shore, Cornell, Robinson, and Ward (1991) concluded that there is strong research support for the need for career education for the gifted, and that this includes good evidence for the differentiation of this provision from career education for all children. Milgram (1991) suggested some of the ways that the content of vocational programs for gifted students should be qualitatively different, for example, addressing why people work, benefits and lifestyles related to different careers, and moral issues associated with certain careers.…”
Section: Vocational Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…See Shaughnessy (1989) for mentoring the creative child and adult which explores the process of assisting or mentoring such students. Shaughnessy and Neely (1990) have explored the personological concerns relative to mentoring. And Siegel and Shaughnessy (1992) have explored the realm of mentoring gifted female students.…”
Section: Mentoringmentioning
confidence: 99%
“…It has featured, albeit in an embryonic form, in the UK since the early 1980s and ourished after Topping (1988) consolidated a variety of practices. Subsequently, there have been variations on the theme of pupil mentoring ranging from peer reading support programmes, mentoring to support disabled pupils (Quicke, 1986), personal support and challenge for gifted pupils (Shaughnessy et al, 1991), mentoring ethnic minority groups (Rodney, 1993) and mentoring as a vehicle for tackling bullying (Sharpe, 1996). Subsequent to these studies, Batty et al (2000) documented a project where high achieving older girls from a Local Education Authority (LEA) high school in Lincolnshire acted as mentors to younger pupils in Year 8 of the same school.…”
Section: Introductionmentioning
confidence: 99%